ChemInform Abstract: LiSbS2‐mC16: Structure Determination from X‐Ray Powder Diffraction Data. Issue 37 (16th September 2014) - Huber, Sebastian; Pfitzner, Arno
Abstract Monoclinic LiSbS2 is prepared by reaction of Li2S, Sb, and excess S as reactive flux (graphite crucible in evacuated silica ampoule, 900 °C, 3 weeks).